Viral diagnostics and analysis of host response to viral infection using microarray technology - Chen, Hui (2014)
Viruses are major factors of human infectious diseases. They not only threaten the public health but also cause economic loss in the worldwide. Microarray, as an advanced technology, has been extensively applied in pathogen detection and host transcriptomic examination upon pathogen infection in the field of virology. During these studies, multiple bioinformatics tools are applied in data interpretation.